(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the convergence of digital marketing and AI data science, examining their scope, applications, and impact on the marketing industry. The paper reviews existing literature to understand the key findings and insights related to these fields. The scope of digital marketing is examined, highlighting its advantages such as precise audience targeting, real-time analytics, and global reach. The paper also delves into the scope of AI data science, emphasizing its role in personalization, campaign optimization, and data-driven decision-making. Based on the review of literature, the findings showcase how digital marketing enables businesses to target specific audiences, measure campaign effectiveness, and expand their reach globally. Meanwhile, AI data science empowers businesses to deliver personalized experiences, optimize marketing campaigns, and gain valuable insights from data analysis. The paper concludes that businesses embracing digital marketing and AI data science can navigate the dynamic and competitive digital landscape more effectively, driving business growth and gaining a competitive advantage. It emphasizes the need for businesses to stay updated with the latest trends and advancements in these fields to maximize their potential.